Notes on the Biology of the Cixiid Planthopper Cixius meridionalis (Hemiptera: Fulgoroidea) - M. L. Bowser (Psyche: A Journal of Entomology)
With the exception of a handful of economically important species, the biology of cixiid planthoppers (Hemiptera: Fulgoroidea: Cixiidae) is poorly known. The host plants and life history of Cixius meridionalis Beirne were investigated in a wetland in Soldotna, Alaska. Specimens were collected over the course of the growing season by hand, aspirator, Berlese funnel, and sweep net. A handful of live nymphs were placed in a terrarium containing potential host plants for direct observation of feeding. C. meridionalis was found to feed on roots of Picea mariana (Mill.) Britton, Sterns & Poggenb, Empetrum nigrum L., Chamaedaphne calyculata (L.) Moench, and Vaccinium vitis-idaea L. At least within the study area, C. meridionalis appears to require multiple years to reach adulthood, with overwintering in nymphal instars. C. meridionalis was occasionally tended by Myrmica alaskensis Wheeler.